Purification and characterization of a feruloyl esterase from the intestinal bacterium Lactobacillus acidophilus - Wang, X; Geng, X; Egashira, Y; Sanada, H (Applied and Environmental Microbiology, 2004)
Dietary ferulic acid (FA), a significant antioxidant substance, is currently the subject of extensive research. FA in cereals exists mainly as feruloylated sugar ester. To release FA from food matrices, it is necessary to cleave ester cross-linking by feruloyl esterase (FAE) (hydroxycinnamoyl esterase; EC 3.1.1.73). In the present study, the FAE from a human typical intestinal bacterium, Lactobacillus acidophilus, was isolated, purified, and characterized for the first time. The enzyme was purified in successive steps including hydrophobic interaction chromatography and anion-exchange chromatography. The purified FAE appeared as a single band in sodium dodecyl sulfate-polyacrylamide gel electrophoresis, with an apparent molecular mass of 36 kDa. It has optimum pH and temperature characteristics (5.6 and 37°C, respectively). The metal ions Cu2+ and Fe3+ (at a concentration of 5 mmol liter-1) inhibited FAE activity by 97.25 and 94.80%, respectively. Under optimum pH and temperature with 5-O-feruloyl-L-arabinofuranose (FAA) as a substrate, the enzyme exhibited a Km of 0.0953 mmol liter-1 and a Vmax of 86.27 mmol liter-1 min-1 mg-1 of protein. Furthermore, the N-terminal amino acid sequence of the purified FAE was found to be A R V E K P R K V I L V G D G A V G S T. The FAE released FA from O-(5-O-feruloyl-alpha-L-arabinofuranosyl)-(1 to 3)-O-beta-D-xylopyranosyl-(1 to 4)-D-xylopyranose (FAXX) and FAA obtained from refined corn bran. Moreover, it released two times more FA from FAXX in the presence of added xylanase.